Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Imigrasi Kelas I Non TPI Depok - Annisa Eka Aprilia; Ratnawaty Marginingsih; Wiwit Rohaeni Yulianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of work motivation and work discipline on employee performance at the Class I Non TPI Depok Immigration Office. The background of the study is based on the importance of the role of human resources in increasing organizational productivity. The method used is quantitative with data collection techniques through questionnaires to the entire population of 83 respondents using a saturated sampling method. Data analysis was carried out using multiple linear regression with the help of SPSS version 21. The results of the T-test of the study obtained showed that work motivation has a positive and significant effect (T count > T table), work discipline has a positive and significant effect (T count > T table) indicating that work motivation and work discipline have an important role in improving employee performance. The results of the F test show that work motivation and work discipline have a simultaneous effect on employee performance (F count > F table) at the Class I Non TPI Depok Immigration Office. The coefficient of determination test of 0.264 employee performance is explained by work motivation and work discipline.